PENDEKATAN KUANTITATIF DALAM PEMETAAN KENYAMANAN JALAN MENGGUNAKAN INTERNATIONAL ROUGHNESS INDEX (IRI) KENDARAAN RODA DUA: PENDEKATAN KUANTITATIF DALAM PEMETAAN KENYAMANAN JALAN MENGGUNAKAN INTERNATIONAL ROUGHNESS INDEX (IRI) KENDARAAN RODA DUA - Pangesti, Rendy Dwi; Pratiwi, Nabila Ayu; Rahmadani, Rani; Suala, Reyhan Tobias Victorio (Politeknik Negeri Semarang, 2025)
The condition of a road section can be known using the IRI (International Roughness Index) value. IRI is the value of the unevenness of the road surface and is determined by the total length of elevation and subsidence of the road surface per unit length. This study aims to evaluate the conditions of road sections in Tembalang District using IRI. IRI data collection using a technology-based vibration sensor method using the RoadLabPro application on a smartphone installed on a two-wheeled vehicle, effectively reaches remote, narrow areas, and various road conditions with high flexibility. The collected data is analyzed to classify road conditions into Good (IRI ≤ 4.0), Moderate (4.1≤IRI≤8.0), Lightly Damaged (8.1≤IRI≤12.0), or Severely Damaged (12≤ IRI). Of the 31 road sections tested, 54.84% were in the Good category with an average IRI value of 3.48 m/km, and 45.16% were in the Moderate category with an average IRI value of 4.89 m/km. Analysis using QGIS serves to map road conditions, identify locations with high IRI values ​​that require repair. The results of this study are expected to be used for more effective road maintenance planning and management, contribute to improving the quality of road infrastructure in Tembalang District, and support decision making to improve the comfort and safety of road users.